Raised circulating Neurokinin A predicts prognosis in metastatic small bowel neuroendocrine tumours. Lowering Neurokinin A indicates improved prognosis. (March 2016) - Ardill, Joy ES; McCance, David R; Stronge, Wendy V; Johnston, Brian T
Background: Assessing prognosis is important in patients with neuroendocrine tumours of the small bowel as disease progression and survival is variable. We previously identified raised Neurokinin A as an independent indicator of poor prognosis and have shown that prognosis worsens when circulating Neurokinin A rises ≥50 ng/L. In the present study we have examined survival in relation to Neurokinin A concentrations. Methods: Patients in whom Neurokinin A rose ≥50 ng/L between January 1989 and December 2010 were identified. All circulating Neurokinin A concentrations were recorded and survival was followed up to 31 December 2014 or to death. Results: Median survival, from the date when Neurokinin A was first ≥50 ng/L was 11.1 (2.0–117.8) months if Neurokinin A remained ≥50 ng/L and 72.4 (4.8–152.6) months when Neurokinin A was reduced below 50 ng/L and controlled below that concentration for ≥3 months (P < 0.001). Survival was significantly better for patients attending the neuroendocrine tumour specialist clinic than for those not attending (P = 0.009). Comparing patients identified during 1989–2000, and those during 2001–2010, Neurokinin A was successfully reduced in the earlier period in 30.3% patients with median survival 23.2 (2.0–152.6) months and this improved in 58.1% with median survival of 43.3 (2.0–141.1) months in the later period (P = 0.019). Significance was greater between the earlier and later periods when only patients attending the neuroendocrine tumour clinic were compared (P = 0.016). Conclusions: Circulating Neurokinin A ≥ 50 ng/L is a strong indicator of poor prognosis when Neurokinin A remains above this concentration. Lowering Neurokinin A below 50 ng/L indicates a significant improvement in prognosis (P < 0.001). This prognostic indicator reflects improved treatment and survival in more recent years.